Capital Structure and Small Growth Firms - Edgar Norton (Journal of Small Business Finance, 1991)
Capital structure choices and preferences in small, rapidly growing corporations are examined. As much of capital structure theory involves variables not easily or practically quantified (e.g., preferences, motivations, agency costs, information asymmetries) a survey was designed in an attempt to gauge the relevance of several theories of capital structure. The survey was sent to 405 firms, taken from lists of successful high growth corporations; 27.2% returned usable responses. Analysis of the responses indicates that tax factors and management preferences have major impacts on capital structure. Implications arising from agency cost, information asymmetry, and signaling theory apparently have little impact on capital structure choice and financing strategies of the responding firms.
Keywords: G32; L25; 650; Capital Structure; Capital; Small Firm; Growth Firm